2019
DOI: 10.3390/molecules24183256
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq Based Transcriptome Analysis of the Anti-Obesity Effect of Green Tea Extract Using Zebrafish Obesity Models

Abstract: Green tea is a popular beverage that is rich in polyphenolic compounds such as catechins. Its major content, (-)-epigallocatechin-3-gallate, has been shown to have beneficial effects on several diseases including cancer, metabolic syndrome, cardiovascular diseases, and neurodegenerative diseases. The aim of this study was to assess the anti-obesity effects and the underlying molecular mechanisms of green tea extract (GTE) using zebrafish larva and adult obesity models. We administered 100 μg/mL GTE to zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
(53 reference statements)
3
21
0
9
Order By: Relevance
“…NP08 (GTE) is well-known for its anti-obesity effects through its bioactive constituents such as (-)-epigallocatechin-3-gallate and (-)-epigallocatechin in rodent models [ 21 , 22 , 23 ]. Additionally, several studies have demonstrated the anti-obesity effects of GTE in zebrafish models [ 13 , 16 , 24 ], which are consistent with our results. In humans, continuous ingestion of a GTE significantly reduces body weight and body fat mass [ 25 ], while Huang et al reported that GTE reduced only serum low-density lipoprotein cholesterol, and did not affect body weight or other blood lipids [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…NP08 (GTE) is well-known for its anti-obesity effects through its bioactive constituents such as (-)-epigallocatechin-3-gallate and (-)-epigallocatechin in rodent models [ 21 , 22 , 23 ]. Additionally, several studies have demonstrated the anti-obesity effects of GTE in zebrafish models [ 13 , 16 , 24 ], which are consistent with our results. In humans, continuous ingestion of a GTE significantly reduces body weight and body fat mass [ 25 ], while Huang et al reported that GTE reduced only serum low-density lipoprotein cholesterol, and did not affect body weight or other blood lipids [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…After a 1-day high-fat diet feeding (HFD), Nile Red (NR) staining was performed (day 1). The NR-stained visceral adipose tissue (VAT; red color) was significantly ( p < 0.01) increased in zebrafish fed a HFD compared to those fed a normal diet (ND; Figure 1 b), as shown previously [ 16 ]. Then, the zebrafish were exposed to test the NPs (100 μg/mL) for 48 h, and NR imaging was conducted again (day 3) to compare the NR intensities of the VAT before and after treatment (day 3/day 1).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…To remove artefacts (eyes and shadows around the yolk sac) from the images, we set the "analyze particles" parameter with an appropriate pixel size limit. For the Nile Red experiment, the integrated density of each image was measured as Nile Red fluorescent intensity using ImageJ, following the methodology used in a previous study [37].…”
Section: Measurement Of Pigmentation In Zebrafish Larvaementioning
confidence: 99%